Knowledge, attitudes, and practices toward assisted reproductive technology and painless egg retrieval among infertile women in the northwest region of China - Zhang, Qiaomei; Wang, Jing; Li, Ting; Wang, Xiaofei; Geng, Juan (Frontiers in Public Health, 2025)
BackgroundWith the increasing use of assisted reproductive technology (ART) as a solution for infertility, understanding patient knowledge, attitudes, and practices (KAP) is essential. This study aimed to assess the KAP of infertile women in Northwest China regarding ART and painless egg retrieval.MethodsThis cross-sectional study enrolled infertile female population in the Northwest Region of China from April to September.ResultsA total of 403 participants were included, with scores of 12.16 ± 5.63 (range: 0–20) for knowledge, 34.30 ± 4.38 (range: 10–50) for attitudes, and 25.28 ± 4.89 (range: 7–35) for practices. Spearman correlation analysis demonstrated the positive correlations between KAP (r = 0.246–0.589, P < 0.001). Structural equation modeling (SEM) showed that knowledge and attitudes are key predictors of practices. Notably, knowledge not only directly influenced practice (β = 0.33, P < 0.001) but also had an indirect effect through its positive impact on attitudes (β = 0.02, P = 0.007).ConclusionInfertile women in Northwest China have moderate KAP scores. To improve their adoption of ART, interventions should focus on enhancing their knowledge and improving their attitudes. Tailored support systems, including improved doctor-patient communication and peer support, are particularly vital for women with lower education and less experience with ART.